Efficacy of fucoxanthin extract from Sargassum horneri on 3T3-L1 pre-adipocyte differentiation: Effects of Fucoxanthin on 3T3-L1 differentiation. - Park, Jeong-Woong; Kang, Kyung Soo; Ha, In Su; Lee, Sang In; Shin, Sangsu (Cellular and Molecular Biology, 2023)
Obesity, a chronic disease characterized by excessive body fat accumulation, is associated with significant health risks. The state of being overweight or obese leads to a number of chronic diseases, including cardiovascular disease, type 2 diabetes, cancer, and osteoarthritis. Accordingly, the regulation of adipocyte proliferation and differentiation has been the focus of many studies. The goal of the present study was to investigate the function of fucoxanthin, extracted from Sargassum horneri, in adipocyte (3T3-L1 cells) differentiation. A quantitative real-time polymerase chain reaction was conducted to investigate the mRNA expression levels of adipocyte differentiation-related genes under fucoxanthin stimulation. All adipocyte-related genes responded to PIC stimuli. Additionally, using western blotting, we confirmed that fucoxanthin reduced adipocyte differentiation. These results indicate that fucoxanthin extracted from Sargassum horneri can regulate adipogenesis. Further studies are needed to reveal the signaling pathways that lead to reduced adipocyte differentiation induced by fucoxanthin.